Towards a Radical Psychotherapy (Existential Analysis: Journal of the Society for Existential Analysis, 2017)
This paper considers the way in which perceptions of the 'other' change with the socio-cultural and physical environments that encompass our experiences. Using concepts from the Sartrean tradition, I argue that when we facilitate change in the way that another person experiences the world, we are acting both politically and from a radical perspective.
Keywords: Anxiety; consciousness; self; other; authenticity; political; radical; psychotherapy.